La ratifica dell’accordo italo-libico (1957). Un cinquantenario di grande rilievo - Vedovato, Giuseppe (Rivista di studi politici internazionali, 2008)
ABSTRACT - Fifty years after the Italian Parliament ratified the agreement between Italy and Lybia of 2nd October 1956, Giuseppe Vedovato, both as a scholar and a protagonist, has revisited an episode fraught with difficulty. The Italian settlement in Lybia had developed over several generations, including «a private colonization, of both capitalists and workers» during the Liberal period, and the very different «demografic colonization» of the Fascists, in which both settlers and State companies had worked side by side to modernize the poor and morphologically diverse territories. If, thanks to the war, the Italian community there underwent periods of enormous uncertainty, the 1947 treaty did not even settle the doubts the victors felt about Lybia’s autonomy and the obvious practical difficulties to self-government in the immediate future. Carlo Sforza’s diplomatic efforts to secure a mandate, as laid down in the UN resolutions and decisions between 1949 and 1951, ran parallel to the debates within Lybia between those who wanted the Country’s unification - some supporting independence and some a federal government – and those who supported the West. The outcome was determined by the ‘good will’ mission Vedovato undertook between Novembre and December 1953 visiting ten Arab Countries, most importantly Lybia. Other meetings, both official and private, helped to carry the negotiations forward until, on 2nd October 1956, the agreement between Italy and Lybia on «economic collaboration and a settlement of the issues» relative to the UN resolution was signed. Its ratification by the Italian Parliament, to which Vedovato contributed with great energy, revealed the positions of the various parties in opposition, but, at the same time, helped to obtain a substantial majority, to the great relief of the Italian community in Lybia, which saw this as a guarantee of its identity and even of its very existence. RÉSUMÉ - A l’occasion du cinquantenaire de la ratification par le Parlement italien de l’accord entre l’Italie et la Libye du 2 Octobre 1956, Giuseppe Vedovato, en spécialiste et protagoniste, nous restitue un épisode difficile de l’histoire de l’Italie. L’implantation italienne en Libye était enracinée depuis plusieurs générations, entre «colonisation privée de la part du monde de la finance et de celui du travail» de la période libérale et, en contradiction, le «colonialisme démographique» fasciste: colons et administrations publiques s’étaient engagés à moderniser des territoires pauvres et difficiles du point de vue morphologique. Si, avec la guerre, la communauté italienne souffrit de grandes incertitudes, le traité de paix de 1947 ne dissipa pas les doutes des vainqueurs, partagés entre la perspective de l’autonomie libyenne et l’impossibilité objective de la réaliser en peu de temps. Les négociations de Carlo Sforza pour aboutir à une administration fiduciaire, dans le cadre des résolutions et des décisions de l’Onu, allèrent de pair avec le dur débat libyen entre unitaristes et indépendantistes et fédéralistes philo-occidentaux. La mission de «bonne volonté» ou «d’amitié» que Vedovato effectua dans dix Pays arabes et en particulier en Libye, entre Novembre et Décembre 1953, fut déterminante. Des contacts officiels et privés favorisèrent la négociation qui put aboutir, le 2 Octobre 1956, à l’accord italo-libyen de «collaboration économique et de règlement des questions qui résultent» de la résolution de l’Onu. La ratification parlementaire, à laquelle contribua Vedovato avec grande détermination, mit en évidence les différentes orientations de l’opposition par rapport au gouvernement, mais en même temps elle obtint une majorité importante, avec le soulagement d’une communauté qui voyait dans ces territoires une grande partie de son identité et de son existence.